Star the little farm cat - Moonheart, Ella (Moonheart, Ella. Kitty's magic, 2018)
While visiting her aunt and uncle's farm, Kitty uses her ability to transform into a cat to find out why her cousin, Max, is so unfriendly and helps with a mouse problem.